HUBUNGAN TINGKAT PENGETAHUAN DENGAN KETERAMPILAN MENYIKAT GIGI PADA IBU HAMIL DI PUSKESMAS ABIANSEMAL III KABUPATEN BADUNG TAHUN 2023 - Ni Nyoman Dewi Supariani; Asep Arifin Senjaya; Ni Made Sirat; I Nyoman Wirata; Suci Nirmala (Jurnal Kesehatan Gigi (Dental Health Journal), 2023)
Pregnant women are one of the groups that are susceptible to dental and oral disease. The level of knowledge, attitude, and behavior of pregnant women can affect oral and dental health. The behavior that is often encountered is the time and way of brushing your teeth that are not right. This study aims to determine the level of knowledge and skills of brushing teeth in pregnant women at the Puskesmas Abiansemal III, Badung Regency 2023. This research is a descriptive research with survey design. The data used in this study were primary data and secondary data, by providing 20 questions and observation of brushing skills using a checklist. The results of this study totaling 31 pregnant women showed that the level of knowledge of brushing teeth was the most with sufficient criteria of 16 people (51.61%), good criteria as many as nine people (29.03%), and at least with less criteria of six people (19.36%). The percentage of brushing skills with the highest frequency was found in the criteria needing guidance, which was 14 people (45.16%), while the lowest frequency was found in the very good criteria, which was two people (6.45%). The conclusion of the results shows that, the average knowledge of respondents is 70 with sufficient criteria. The average skill of respondents was 58.39 with the criteria of needing guidance. In respondents who have a good level of knowledge, the majority have good criteria skills.